Genetic analysis and qtl mapping of brown planthopper (Nilaparvata lugens stål.) biotypes 2 and 3 resistance in rice - Shabanimofrad, Mahmoodreza (2015)
The use of molecular markers in many aspects of rice (Oryza sativa L.) studies such as genetic analysis of insect and diseases resistance genes is on the increase. Molecular markers have played an important role in rice breeding worldwide. Brown planthopper (BPH),Nilaparvata lugens is one of the most destructive insect pests in rice growing areas of the world. Several strategies such as QTL mapping are being deployed in breeding for resistance genes into rice varieties have been proposed for combating the BPH insect pest. This study used molecular marker approach in order to analyse molecular genetics of resistance in segregating populations and to identify QTL conferring resistance against two different biotypes of brown planthopper, namely, Biotype 2 and 3, in F3 generation families derived from the cross between Rathu Heenati (BPH resistant) and MR276 (BPH susceptible) cultivars. One hundred and ten SSR primer pairs related to BPH resistance gene (Bph genes) distributed over 12 chromosomes of the rice genome were chosen and used to amplify SSR markers, and to analyse their potential association with Bph resistance. Fifty seven of polymorphic markers were used to identify BPH resistant segregation ratios in 176 individuals of F2 population. Thirty five markers showed a good fit to the expected segregation ratio (1:2:1) for single gene model (df = 1.0, p ≤ 0.05). The rest of the markers did not fit the expected segregating Mendelian ratios. The F3 generation families were grown in a greenhouse and infested with two BPH biotypes, Biotype 2 and 3. Chi-square analysis showed a good fit to the phenotypic ratio of 3:1 for the segregation of resistance and susceptibility for the Biotypes 2 and 3 of BPH. Six SSR markers, RM401, RM5953, RM217, RM210, RM242 and RM1103 were found significantly associated with resistance to Biotype 2 and 3 of BPH in rice. These markers showed high selection accuracy for resistant plants with confirmation of resistance effect of about 17 and 20% respectively for phenotypic variation, and can be used in MAS for the resistant gene. The resistance gene markers reported here provide rice breeders and geneticists a valuable tool for markerassisted selection of the BPH insect resistance gene. A total of 150 F3 generation families derived from the cross between Rathu Heenati and MR276 were used in this experiment to identify QTLs for resistance to BPH Biotypes 2 and 3. A trait distribution analysis showed continuous variation with normal distribution. Twenty independent QTLs were detected to be associated with BPH resistance on nine chromosomes. Five putative QTL (qBph-1-1,qBph-3-1, qBph-6-1, qBph-7-1 and qBph-3-1) with Logarithmic of Odds (LOD) > 3.0 and five suggestive QTLs (qBph-5-1, qBph-11-1, qBph-6-1, qBph-9-1 and qBph-12-1, LOD <3.0) were detected for Biotype 2. Meanwhile, two putative QTLs (qBph-3-1 and qBph-6-1) with LOD > 3.0 and eight suggestive QTLs (qBph-1-1, qBph-7-1, qBph-6-1, qBph-9-1,qBph-3-1, qBph-6-1, qBph-10-1 and qBph-12-1, LOD < 3.0) were detected for Biotype 3. The individual locus found in the F3 population for traits studied, explained 7 to 24% of the total phenotypic variance in resistance against BPH biotypes. In conclusion, from this research, the QTL identified could help breeders in their programme for marker-assisted selection for rice varietal development with BPH resistance.